Tetrabutylammonium fluorochromate(VI) (TBAFC): a mild and efficient reagent for oxidation of organic substrates - SHAHRIARE GHAMMAMI; SEYED ABOLFAZL SEYED SAJADI (Journal of the Serbian Chemical Society, 2005)
Orange solid tetrabutylammonium fluorochromate, (C4H9)4NCrO3F, TBAFC, is easily synthesized by the reaction of tetrabutylammonium fluoride with CrO3 in a 1:1 mole ratio. Tetrabutylammonium fluorochromate(VI) is a versatile reagent for the effective and selective oxidation of organic substrates, in particular of alcohols, under mild conditions. The facile oxidation of triphenylphosphine to triphenylphosphine oxide by TBAFC in CH3CN provides clear evidence for an oxygen-transfer reaction.